Ennis Franciscan Friary, loose fragments, window head - O'Donovan, Danielle (My University, 2008)
Fragment of ogee headed window under a square label. The moulding can be read as: frontal roll-and-fillet flanked by hollow chamfers, after this broken at one side and with a quadrant at the other. Or, it can be read, from intrados, as comprising: quadrant, hollow chamfer, quadrant, fillet, quadrant, hollow chamfer.
ogee window
Keywords: quadrant; Architecture, Gothic -- Ireland; Ennis (Ireland)--Buildings, structures, etc.; Architecture, Franciscan; Late Medieval; fillets (moldings); roll moldings; moldings, hollow; roll-and-fillet moldings; labels (moldings)